Biodiversitas Jenis Ikan di Perairan Sungai Kabupaten Pesisir Selatan, Provinsi Sumatera Barat - Masrizal, Masrizal; Endryeni, Endryeni; Mayasari, Lisa (Mantis Journal of Fisheries, 2026)
This study aimed to determine fish diversity and assess water pollution in rivers of Pesisir Selatan Regency, West Sumatra, using fish as bioindicators. Conducted from April to October 2024 in six rivers, sampling used cast nets, gill nets, scoop nets, and traps. A total of 25 species were identified, belonging to 4 orders, 13 families, and 20 genera. The most dominant group was garing fish (genus Tor) at 24.08%, while lais fish (Ompok leiacanthus) was the least (0.33%). The diversity index (H = 2.6637–3.0358) indicates moderate to high diversity, with even distribution (E = 0.8981–0.9701), low dominance (D = 0.0550–0.0853), and high species richness (R = 2.8854–3.3762). Overall, river conditions are classified as lightly polluted based on diversity index values (2 < H < 3).